The tentacles of majoritarianism: How far can they reach into retrenchment? - Le Roux, Rochelle (Obiter, 2020)
Majoritarianism enables a trade union with a majority in the workplace to prevail over minority unions and their members as well as non-unionised employees and to limit some of the minority’s rights, including the right to strike. This article revisits the basic tenets of majoritarianism and calls for a more nuanced distinction between legislative provisions giving special privileges to majority unions and those provisions that enable majority unions to prevail over minority unions. Ultimately, the focus of the article is on the interface between majoritarianism and retrenchment. While it argues that there is legitimate scope for a collective agreement concluded after retrenchment consultations to be extended to the members of minority unions, the article expresses reservations whether a collective agreement regarding the identity of consulting parties in the case of retrenchment can similarly be extended. Nonetheless, the article concedes that the model of majoritarianism informing the Labour Relations Act (LRA) possibly lacks the subtlety to accommodate this distinction.